Steam: Volatile Constituents from Cymbopogon pospischilli - Joshi, Alka (Indian Forester, 1996)
The grass Cymbopogon occurs in tropical subtropical and mountain grassland and arid zones. The grass C. pospischilii has not previously been reported to grow in the North-western region of Uttar Pradesh. This is the first report of its wild growth in Garhwal region. The chemical study of its oil reveals that it is rich in monoterpene alcohol.